Ethical and Legal Concerns Associated With Withdrawing Mechanical Circulatory Support: A U.S. Perspective - Mueller, Paul S. (Frontiers in Cardiovascular Medicine, 2022)
Hundreds of thousands of Americans have advanced heart failure and experience severe symptoms (e.g., dyspnea) with minimal exertion or at rest despite optimal management. Although heart transplant is an effective treatment for advanced heart failure, the demand for organs far exceeds the supply. Another option for these patients is mechanical circulatory support (MCS) provided by devices such as the ventricular assist device and total artificial heart. MCS alleviates symptoms, prolongs life, and provides a “bridge to transplant” or a decision regarding future management such as “destination therapy,” in which the patient receives lifelong MCS. However, a patient receiving MCS, or his/her surrogate decision-maker, may conclude ongoing MCS is burdensome and no longer consistent with the patient’s healthcare-related values, goals, and preferences and, as a result, request withdrawal of MCS. Likewise, the patient’s clinician and care team may conclude ongoing MCS is medically ineffective and recommend its withdrawal. These scenarios raise ethical and legal concerns. In the U.S., it is ethically and legally permissible to carry out an informed patient’s or surrogate’s request to withdraw any treatment including life-sustaining treatment (LST) if the intent is to remove a treatment perceived by the patient as burdensome and not to terminate intentionally the patient's life. Under these circumstances, death that follows withdrawal of the LST is due to the underlying disease and not a form of physician-assisted suicide or euthanasia. In this article, frequently encountered ethical and legal concerns regarding requests to withdraw MCS are reviewed: the ethical and legal permissibility of withholding or withdrawing LSTs from patients who no longer want such treatments; what to do if the clinician concludes ongoing LST will not result in achieving clinical goals (i.e., medically ineffective); responding to requests to withdraw LST; the features of patients who undergo withdrawal of MCS; the rationale for advance care planning in patients being considered for, or receiving, MCS; and other related topics. Notably, this article reflects a U.S. perspective.